1949. Evaluation of cellular and humoral immune-responses at different times after SARS-COV-2 vaccination in health care workers cohort. (15th December 2022) - Dentone, Chiara; Fenoglio, Daniela; Cerchiaro, Matteo; Ponzano, Marta; Altosole, Tiziana; Franciotta, Diego; Portunato, Federica; Mikulska, Malgorzata; Taramasso, Lucia; Magnasco, Laura; Uras, Chiara; Magnè, Federica; et al.
Abstract: Background: We studied immunological response against SARS-CoV-2 after two doses of vaccine in health care workers (HCW) at our Infectious Disease Unit Methods: We enrolled prospectively HCW without (group A) and with previous infection (group B). We collected peripheral blood at baseline (before the BNT162b2 vaccine), T1 (before the 2 nd dose), T2 and T6 (after 1 and 6 months after of 2 nd dose). The activation induced cell marker assay (AIM) was performed with CD4 and CD8 Spike peptide megapools (MPs). We evaluated the Stimulation Index (SI) as AIM+ stimulated cells/negative control (positive response SI >= 2). Quantitative antibodies (Abs) to Spike-1 protein (S) and to nucleocapside protein (N) were detected with an electrochemiluminescence immunoassay. We tested at T6 the responses to alpha, beta, gamma, delta and epsilon variants MPs.We used the linear mixed model with random intercept adjusted for age and sex to compare specific times to T0. To assess differences over time between groups the interaction with time was tested. Results: In group A 13/22 (59%) were female vs 5/7 (71%) group B, the mean age 40 vs 38 years, respectively. For CD4+ Spike the overall rate of change over time was significant at T1 (p=0.038) and at T2 (p< 0.001) vs T0 with a decreasing at T6 (p not significant) [Figure 1 ] with a trend of higher response in group A. In group B the CD8+ Spike reactivity increased at T1(p=0.037) and at T6 (p=0.005) vs T0. The interaction between SI and time was statistically significant at T1 (p=0.033); T2 (p= 0.046) and T6 (p=0.035) (mean values in group B higher than A). For overall population, the anti-S Abs significantly increased at T1 vs T0, T2 vs T0 and at T6 vs T0 [Figure 2A ]. The group B at T6 retained a higher anti S response but the rate of change significantly differs between the two group (overall interaction: p< 0.001) [Figure 2B ]. At T6 in both groups we found a high CD4+ T cells response to epsilon variant, even if not detected as circulant virus. Quantitative (U/ml) values of anti-S Antibodies. Conclusion: The humoral response was persistent and increased in previous infected subjects. The CD4+T cells response after vaccination retained a response in uninfected subject, with an increasing trend and with a response to non-circulating variants. The vaccine could help the CD8+ T cells reactivity specific for Spike peptides. Disclosures: Chiara Dentone, CD, Angelini: Advisor/Consultant|Gilead: Advisor/Consultant|Menarini: Advisor/Consultant|Novartis: Advisor/Consultant Lucia Taramasso, LT, Gilead: Advisor/Consultant|Janssen: Advisor/Consultant|ViiV: Advisor/Consultant Alessandro Sette, AS, Arcturus Therapeutics: Grant/Research Support|Astrazeneca: Advisor/Consultant|Avalia: Advisor/Consultant|CellCarta: Grant/Research Support|Flow Pharma: Grant/Research Support|Fortress: Advisor/Consultant|Gritstone Bio: Advisor/Consultant|ImmunoScape: Advisor/Consultant|Moderna: Advisor/Consultant|Repertoire: Advisor/Consultant Antonio Di Biagio, AD, Abbvie: Advisor/Consultant|Gilead: Grant/Research Support|Janssen: Advisor/Consultant|MSD: Advisor/Consultant|ViiV: Advisor/Consultant Matteo Bassetti, PhD, Angelini: Advisor/Consultant|Astellas: Grant/Research Support|Bayer: Advisor/Consultant|Bayer: Honoraria|BioMe ́ rieux: Advisor/Consultant|BioMe ́ rieux: Honoraria|Cidara: Advisor/Consultant|Cidara: Honoraria|Cipla: Advisor/Consultant|Cipla: Honoraria|Gilead: Advisor/Consultant|Gilead: Honoraria|Menarini: Advisor/Consultant|Menarini: Honoraria|MSD: Advisor/Consultant|MSD: Honoraria|Nabriva: Advisor/Consultant|Pfizer: Advisor/Consultant|Pfizer: Board Member|Pfizer: Grant/Research Support|Pfizer: Honoraria|Shionogi: Advisor/Consultant|Shionogi: Honoraria|Tetraphase: Advisor/Consultant.